Analysis of the Merdeka Belajar Curriculum Assessment in Strengthening the Pancasila Student Profile - Gamar Al Haddar Gamar; Eka Selvi Handayani; Aryanthi Jhon; Jesita Melina Tika Mera (The Future of Education Journal, 2024)
The purpose of this study is to analyze teacher assessment in the Merdeka Belajar curriculum. This research is a qualitative study. Data collection techniques were conducted through interviews and documentation. Data analysis was performed through data reduction, data presentation, and conclusion drawing. The sampling technique used was purposive sampling, and the data validity test was conducted through source triangulation. Based on the results of the study, it was found that SDN 008 Samarinda Ulu has implemented the Merdeka Belajar curriculum in accordance with the government's policy on the Merdeka curriculum at the 1st, 2nd, 4th, and 6th-grade levels for the 2023/2024 academic year. The assessments that have been implemented include diagnostic assessments to explore the initial abilities of students in the classroom. Formative assessments to monitor student learning progress. Formative assessments are conducted after each learning unit to determine students' ability to understand the lessons taught. Summative assessments are carried out in the middle and at the end of the learning period as a report of the final grades obtained by students. The report cards provided in the Merdeka curriculum are simpler, consisting of two types: the intracurricular report card and the Pancasila student project report card. The assessment of the Pancasila student profile strengthening project that has been carried out includes themes such as sustainable lifestyles and local wisdom.